Industrial Training Report: Active Scientific Sdn Bhd / Mohd Zainol Melan - Melan, Mohd Zainol (Faculty of Information Management, 2016)
Based on the period from 01 February 2016 to OJ July 2016 in Active Scientific Sdn Bhd. Disseminate of information are very important in an organization to ensure the smooth work of the management and administration of the organization. Administrative documents and users can share information directly without any problems. Indirectly, this website can improve the efficiency of sharing information to make more easily without any problems. The development of this website in the Internet environment can provide greater convenience for customer to retrieve information regarding products in anywhere and anytime through the Internet. The developed Website was tested in an environment Operations Center or Customer Service Customer Service Operation Center (CSOC), Kuala Lumpur. The results show that the system developed successfully run and manage the website function properly.